IMPACT OF AI TOOLS ON ARTISTIC SKILL DEVELOPMENT IN SCULPTURE - Manhas, Rashmi; Pawar, Aarti Suryakant; Aggarwal, Prateek; Kapila, Ish; Sunitha B J,; Jadhav, Yogesh (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The swift development of artificial intelligence (AI) has brought about revolutionary possibilities to sculpture practice transforming how artists conceptualize, design, and make three-dimensional pieces. The paper explores how AI-related devices are affecting the development of artistic skills in the field of sculpture and how they are affecting the established artisanal abilities as well as the new digital skills. The research analyzes the application of the current sculptural workflow through the integration of technologies into it, including generative design, 3D model, and robotic fabrication. The results have emphasized that the conceptual skill development through AI tools is increased because of the ability to prototype more quickly, visual experimentation is extended, and complex geometries that are hard to build manually can be explored. Nevertheless, there is a growing concern about the practice of maintaining tactile skills, material sensitivity and embodied knowledge that is believed to be part of sculptural practice as a result of the growing dependence on digital assistance. According to the interviews and case studies, a significant portion of artists do not consider AI as a substitute but as a partner that enables a person to expand creativity and facilitates the decision-making process. The research has also established significant consequences to the art education field in that it is necessary to update the curricula to include a balance between digital literacy and manual skills. On the one hand, AI is a chance of innovation and, on the other hand, a challenge that emerging artists have to adapt to the fast-changing technologies.